If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 4x^{2}+ x + -18 = 0 Reorder the terms: -18 + x + 4x^{2}= 0 Solving -18 + x + 4x^{2}= 0 Solving for variable 'x'. Factor a trinomial. (-9 + -4x)(2 + -1x) = 0## Subproblem 1

Set the factor '(-9 + -4x)' equal to zero and attempt to solve: Simplifying -9 + -4x = 0 Solving -9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -4x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -4x = 0 + 9 -4x = 0 + 9 Combine like terms: 0 + 9 = 9 -4x = 9 Divide each side by '-4'. x = -2.25 Simplifying x = -2.25## Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2## Solution

x = {-2.25, 2}

| 3(2y-1)=5-4y | | 3x-7=-2x+4 | | 1-x=4 | | 24x^2-24x^3+0=0 | | 24x^2-24x^3=0 | | 3x^2-4x-7=0 | | x^2-2x-35=0 | | 32x+21y= | | x+3=-4-2x | | x^2-11x+10=0 | | (9x-6)(3x+3)=0 | | 5(3c-2)+8=45 | | 14x+4=19x-8 | | 4(3a+6)=-24 | | 4(31+6)=-24 | | 20=-d+16 | | 9=-x+8 | | 11=-d+15 | | x^4+6x^3+9x^2-4x=12 | | 9d+2d+3d-4=5d | | 2x+4=3x-2 | | 8x^3+18x^2+16x=0 | | 16x^2=100 | | 4x^2+9x+8=0 | | 5x^2=60 | | 7y-23=19+y | | 3x^2=375 | | 2x^2=98 | | x^2=20 | | 3x^2=48 | | 15-4x=27 | | 4X-8=10-2x | | -51t-14=2t | | -51-14=21 | | 5x+4=2x-5 | | 5-3(a+6)=a-1+8a | | 3m-5m-12=7m-88-5 | | x-1=1# | | 4(3x-5)=5x+2(x+15) | | 2(9n-1)+7(9+6)=-60 | | 0.456=-0.3(7n-31.2) | | 4x^3+2x-28=0 | | g-9=19 | | -38=-2(-43d-24) | | 4(x-7)=2x-38 | | -10.1=w+5.3 | | 9r+22r= | | 8x+21=-59 | | 8x+21=59 | | 6x+34=4 | | 8a-3(5+2a)=85-3a | | 4a+3=2a+5 | | 33+5x=2x+75 | | 8c+1=7c-2(7+c) | | 18-4n=8-2(1+8n) | | 6X(3*5)+7(5X*3)=0 | | 6-(3*5)+7(5*3)= | | 6*(3*53)+7(5*3)= | | 6x-1=2x+6 | | 6*(3*5)+7(5*3)= | | 3m(7m+2)=0 | | 2(h+1)-2h+10= | | 5n+3+4n=16 | | 3x-7=2x-9 | | 8(x-8)=2x+8 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics